STRUCTURAL AND STRATIGRAPHICAL RELATIONSHIP IN THE ESTERN PART OF THE DRAVA DEPRESSION - WIDER AREA OF THE FIELD BENIČANCI (Rudarsko-geološko-naftni zbornik, 2015)
This article closely defines the stratigraphic and structural relations within the eastern part of the Drava depression. These relations are explained in detail for the more important fields located in the area of exploration such as Beničanci, Klokočevci, Števkovica and others. A geological column has been synthesized for the Beničanci area together with correlation profiles to better display the lithology of the Lower and Middle Miocene. Furthermore, structural maps of key bed H and EL-markersG, Z',Rρ, α have been developed and interpreted and the stratigraphic-structural relations of the investigation area have been laid down.